2013
DOI: 10.1186/1755-8166-6-25
|View full text |Cite
|
Sign up to set email alerts
|

Distinct mechanism of formation of the 48, XXYY karyotype

Abstract: BackgroundTo expose the unusual nature of a coincident sex chromosomal aneuploidy in a patient and his father. Molecular mechanisms involved probably are based on the sperm chromosome of paternal origin, which determine the mode of formation. Conventional cytogenetics techniques and multiple Quantitative Fluorescent PCR of STR markers in sexual chromosomes in the patient and his parents.Results48,XXYY and 47,XYY aneuploidies in the patient and his father, respectively, were identified. The additional X and Y c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…A mere 1–2% of spermatozoa contain an aneuploidy of sex chromosomes, compared to more than 20% in oocytes ( Martin, 2008 ). While it is possible to produce an XXYY karyotype through nondisjunction during mitosis of a normal fertilized egg, evidence from parental origin studies of XXYY in seven published cases over the past two decades has consistently indicated that the triploid gamete (X p Y p Y p ) is of paternal origin ( Rinaldi et al, 1979 ; Lorda-Sanchez et al, 1992 ; Leal et al, 1994 ; Iitsuka et al, 2001 ; Balsera et al, 2013 ). The origin of the supernumerary chromosomes is important due to a process known as genomic imprinting, wherein the manner in which certain genes are expressed depends upon the parent of origin.…”
Section: Introductionmentioning
confidence: 99%
“…A mere 1–2% of spermatozoa contain an aneuploidy of sex chromosomes, compared to more than 20% in oocytes ( Martin, 2008 ). While it is possible to produce an XXYY karyotype through nondisjunction during mitosis of a normal fertilized egg, evidence from parental origin studies of XXYY in seven published cases over the past two decades has consistently indicated that the triploid gamete (X p Y p Y p ) is of paternal origin ( Rinaldi et al, 1979 ; Lorda-Sanchez et al, 1992 ; Leal et al, 1994 ; Iitsuka et al, 2001 ; Balsera et al, 2013 ). The origin of the supernumerary chromosomes is important due to a process known as genomic imprinting, wherein the manner in which certain genes are expressed depends upon the parent of origin.…”
Section: Introductionmentioning
confidence: 99%